Touchscreens for Whom? Working Memory and Age Moderate the Impact of Contingency on Toddlers' Transfer From Video - Choi, Koeun; Kirkorian, Heather L.; Pempek, Tiffany A. (Frontiers in Psychology, 2021)
Toddlers exhibit poor transfer between video and real-world contexts. Contingently responsive video such as that found in touchscreen apps appears to assist transfer for some toddlers but not others. This study investigated the extent to which toddlers’ working memory moderates the impact of contingency on toddler’s transfer of learning from video. Toddlers (24-36 months; N = 134) watched a hiding event on either (a) contingent video that advanced only after touch input or (b) noncontingent video that proceeded automatically. Toddlers then searched for a corresponding object on a felt board. Additionally, toddlers’ working memory (WM) was assessed. Findings indicate WM and age moderated the impact of contingency on transfer: Contingency decreased transfer in younger children while increasing transfer among older children. However, this was only true for children with relatively low WM. Contingency had little impact on transfer among children with relatively high WM, regardless of age. Results from this study suggest that WM is one specific moderator that predicts whether toddlers are likely to learn from contingent versus noncontingent video, yet WM does not operate in isolation. Together, these findings underscore the importance of considering multiple child characteristics when identifying the optimal conditions for toddlers’ learning from symbolic media.